2019
DOI: 10.1002/ejic.201900936
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Magnesium Hydride Complexes with Neutral Ligands

Abstract: The reaction of Mg[N(SiMe 3 ) 2 ] 2 with PhSiH 3 in benzene at room temperature gave a white precipitate of approximate constitution MgH 1.5 N′′ 0.5 . This undefined hydride rich Mg salt can be dissolved by addition of well-known neutral donors, such as PMDTA, DABCO or the N-heterocyclic carbene I Me iPr (N,N′-diisopropyl-2,3-dimethylimidazol-2-ylidine). This allowed for crystallization and structural characterization of five new magnesium hydride complexes: Mg 2 (μ-H) 2 N′′ 2 ·(PMDTA) (1), Mg 4 (μ-H) 6 N′′ 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…As part of the same study that resulted in the isolation of compound 108 , Harder and coworkers reported that reaction of Mg­[N­(SiMe 3 ) 2 ] 2 with PhSiH 3 in benzene at room temperature gave a white precipitate of approximate constitution MgH 1.5 {N­(SiMe 3 ) 2 } 0.5 , and which could be dissolved by addition of the neutral N -donors N , N , N ′, N ′′, N ′′-pentamethyl­diethylenetriamine (PMDTA) and 1,4-diazabicyclo­[2.2.2]­octane (DABCO) (Scheme ). This procedure enabled the structural characterization of four magnesium hydride complexes, [Mg 2 (μ-H) 2 {N­(SiMe 3 ) 2 } 2 ·(PMDTA)] ( 109 ), [Mg 4 (μ-H) 6 {N­(SiMe 3 ) 2 } 2 ·(PMDTA) 2 ( 110 ), [Mg 5 (μ-H) 7 {N­(SiMe 3 ) 2 } 3 ·(PMDTA) 2 ] ( 111 ), and [Mg 2 (μ-H) 2 {N­(SiMe 3 ) 2 } 2 ·(DABCO) 2 ] ( 112 ) (Scheme ). The PMDTA complexes 109 – 111 were only isolated as inseparable mixtures, whereas compound 112 was isolated in pure form and fully characterized.…”
Section: Molecular Hydrides Of the Group 2 Metalsmentioning
confidence: 78%
See 1 more Smart Citation
“…As part of the same study that resulted in the isolation of compound 108 , Harder and coworkers reported that reaction of Mg­[N­(SiMe 3 ) 2 ] 2 with PhSiH 3 in benzene at room temperature gave a white precipitate of approximate constitution MgH 1.5 {N­(SiMe 3 ) 2 } 0.5 , and which could be dissolved by addition of the neutral N -donors N , N , N ′, N ′′, N ′′-pentamethyl­diethylenetriamine (PMDTA) and 1,4-diazabicyclo­[2.2.2]­octane (DABCO) (Scheme ). This procedure enabled the structural characterization of four magnesium hydride complexes, [Mg 2 (μ-H) 2 {N­(SiMe 3 ) 2 } 2 ·(PMDTA)] ( 109 ), [Mg 4 (μ-H) 6 {N­(SiMe 3 ) 2 } 2 ·(PMDTA) 2 ( 110 ), [Mg 5 (μ-H) 7 {N­(SiMe 3 ) 2 } 3 ·(PMDTA) 2 ] ( 111 ), and [Mg 2 (μ-H) 2 {N­(SiMe 3 ) 2 } 2 ·(DABCO) 2 ] ( 112 ) (Scheme ). The PMDTA complexes 109 – 111 were only isolated as inseparable mixtures, whereas compound 112 was isolated in pure form and fully characterized.…”
Section: Molecular Hydrides Of the Group 2 Metalsmentioning
confidence: 78%
“…In 2019, effectively contemporaneous reports by the groups of Gilliard and Harder demonstrated that the magnesium–hydride complexes, [(ImMe 2 i Pr 2 )­Mg­{N­(SiMe 3 ) 2 }­(μ-H)] 2 ( 107 , ImMe 2 i Pr 2 = (MeCN i Pr) 2 C:) and [(ImMe 2 i Pr 2 )­Mg­(μ-H)­(ASCP)] 2 ( 108 , ASCP = 2,2,5,5-tetramethyl-2,5-disila-1-azacyclopent-1-yl), were accessible by an analogous route to that employed in the synthesis of [(IPr) 2 Mg 4 H 6 {N­(SiMe 3 ) 2 } 2 ] ( 106 , Scheme b). , Both compounds 107 and 108 were shown to exist in the solid state as centrosymmetric dimers with [Mg 2 (μ-H) 2 ] 2+ cores and provided sharp Mg–H singlet resonances at 4.28 and 4.29 ppm in their respective 1 H NMR spectra in C 6 D 6 .…”
Section: Molecular Hydrides Of the Group 2 Metalsmentioning
confidence: 99%
“…S2 †). 4,[7][8][9][13][14][15][16][17][18][19][20][21][22] Compound 3b can also be made using a more facile synthetic route, reacting LH 2 Scheme 1 Synthetic procedure for the formation of compounds 1a, 1b and 2b.…”
Section: Resultsmentioning
confidence: 99%
“…The NPA charges for Mg in 1*-3* compare well to those in recently reported Mg hydride dimer complexes stabilized by the (Me 3 Si) 2 N À anion and neutral Lewis bases: Mg + 1.63/ + 1.67. [65] Charges on the hydrides in the latter Mg hydride dimer (H -0.79) are at the lower end of those in 1*-3*. The NPA charges for Ba in 1*-3* compare well to those in the related (HBaN") 7 cluster (F in Scheme 1) which vary from + 1.68 to + 1.77.…”
Section: Theoretical Considerationsmentioning
confidence: 88%